Teachers’ Perceptions of Online Learning During the COVID-19 Pandemic: Challenges and Opportunities - Ilham Bagus Waskita; Putri Wijayanti; Reza Faizal Huda (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The COVID-19 pandemic forced educators worldwide to rapidly adapt to online learning platforms. This research explores teachers’ perceptions of this transition in a range of subjects and educational levels. Through qualitative interviews with 50 educators, the study identifies key challenges, such as technical difficulties and lack of student engagement, alongside opportunities for innovation and personalized learning. Findings suggest that while online teaching posed significant hurdles, it also provided teachers with new ways to engage students and improve pedagogical practices.